High Performance Space Lubrication of MoS2 with Tantalum (Adv. Funct. Mater. 20/2022). (13th May 2022) - Serles, Peter; Nicholson, Eric; Tam, Jason; Barri, Nima; Chemin, Jean‐Baptiste; Wang, Guorui; Michel, Yann; Singh, Chandra Veer; Choquet, Patrick; Saulot, Aurélien; Filleter, Tobin; Colas, Guillaume
Abstract : Space Lubricants In article number 2110429, Aurélien Saulot, Tobin Filleter, Guillaume Colas, and co‐workers engineer a high‐performance space lubricant for the extreme environments faced by spacecrafts. The co‐deposition of MoS2 with tantalum produces a synergistic effect where the tantalum preferentially oxidizes in terrestrial environments and enhances lubrication in deep space vacuum, resulting in low friction and wear despite the harsh conditions seen by spacecrafts.